EKSISTENSI ADI WIDYA PASRAMAN SUTASOMA DI DISTRIK NABIRE BARAT KABUPATEN NABIRE PROVINSI PAPUA - Aditya Dwianto; Ni Wayan Arini; Ni Wayan Sri Prabawati Kusuma Dewi (UHN IGB Sugriwa Denpasar, 2023)
Hindu religious education can be done by activating pasraman activities. Pasraman itself consists of two, namely formal and non-formal pasraman. Adi Widya Pasraman Sutasoma is the only formal pasraman in Nabire Regency. This Pasraman has the advantage that only Adi Widya Pasraman Sutasoma is a Hindu- based school. so that the Nabire Hindu community felt helped to send their children to Adi Widya Pasraman Sutasoma. This pasraman is not only attended by Hindu students but there are also non-Hindu students who study at this pasraman. Adi Widya Sutasoma Pasraman in Nabire Regency has existed since the 2015 -2016 academic year. It is hoped that this pasraman can strengthen the character of students and can also improve the quality of superior graduates. In accordance with the background of the problems above, what can be studied are (1) the form of Adi Widya Pasraman Sutasoma (2) the obstacles faced and the efforts made by Adi Widya Pasraman Sutasoma (3) the implications of Adi Widya Pasraman Sutasoma. The theories used in this study are (1) structural functional theory, (2) learning theory, and (3) reciprocal stimulation theory. Sources of data used are primary and secondary data. The method used to collect data is observation, interviews, literature study. The data collected was then analyzed by reduction techniques. Presentation of data, concluded and verification of data. The results showed that (1) Adi Widya Pastaman Sutasoma's form was formal pasraman, Adi Widya Pasraman Sotasuma's learning consisted of 40% general group and 60% religious group. (2) the obstacles and efforts of Adi Widya Pasraman Sutasoma in overcoming learning consist of two factors, namely internal and external factors. Meanwhile, its efforts to utilize learning media to overcome internal barriers to students and provide dormitories for students to overcome external obstacles. (3) The implications of Adi Widya Pasraman Sutasoma in the social life of the community, namely the implications for increasing sradha and devotion of the Nabire Hindu Community and implications for religious social life.